PELATIHAN MEMBUAT MEDIA PEMBELAJARAN BAGI GURU PAI MENGGUNAKAN APLIKASI CANVA DESA SEGARAJAYA - Fitri Hermawati; Siti Asiah; Aulia Ayu Rohayah (An-Nizam, 2022)
Teachers have an important role in the process of teaching and learning activities. But unfortunately in this online learning there are still many teachers who have difficulty in making learning patterns through content media. Due to lack of references and several other factors. Therefore, the readiness of teachers to face the digital era in the world of education is very necessary, so that teachers are ready to use digital technology as the main learning platform. By conducting training to make learning videos through the Canva application because it is very important for teachers to do. The goal is for teachers to be able to make videos that are interesting, interactive, easy to understand and useful. In addition, continue to encourage a sense of enthusiasm to teach under any circumstances. The method used is socialization, training and evaluation. The existence of training activities to make learning media can improve the ability of teachers to provide material and teachers are also increasingly able to use technology, are able to make learning videos through YouTube and can implement the Canva application and get new references.